The fetal splenic vein flow pattern and fetal inflammatory response in the preterm prelabor rupture of membranes. (May 2014) - Musilova, Ivana; Kacerovsky, Marian; Andrys, Ctirad; Kostal, Milan; Slaba, Katarina; Jacobsson, Bo
Abstract Objective: To evaluate the intensity of the fetal inflammatory response, characterized by umbilical cord blood IL-6 levels, and neonatal outcome in the preterm prelabor rupture of membranes (PPROM) pregnancies using the pulsatile fetal splenic vein flow pattern. Methods: Women with singleton pregnancies complicated by PPROM at a gestational age between 24 + 0 and 36 + 6 weeks were included in the study. Doppler evaluation of the fetal splenic vein flow was performed. The flow-velocity waveform pattern was evaluated qualitatively as continuous or pulsatile. The umbilical cord blood interleukin-6 (IL-6) levels were evaluated after delivery. The fetal inflammatory response was defined as IL-6 >11 pg/mL. Results: In total, 129 women were included. The fetuses with pulsatile splenic vein flow exhibited higher IL-6 levels in umbilical cord blood (median: 56.7 pg/mL versus 5.6 pg/mL; p < 0.0001) and had a higher rate of fetal inflammatory response syndrome (71% versus 35%; p = 0.0005) than fetuses with continuous flow. The pulsatile flow pattern was related to a higher rate of early onset neonatal sepsis (odds ratio 4.2; 95% confidence interval: 1.3–13.5). Conclusion: The presence of pulsatile fetal splenic vein flow in PPROM pregnancies is associated with fetal inflammatory response and neonatal morbidity.